(untitled) (International Journal of Engineering and Computer Science, 2017)
In this paper we aims to bring up the idea of different platform environment to compare a heterogeneous database system, where it may use different ways of storing like file formats, protocols, query language. The biggest challenge for any organization occurs during migration of large databases, which easily consume more terabytes. In different RDBMS, i.e. oracle database 10g, DB2, SQL Server, MySql and MS access etc where those database are not available previously for high speed migration and also performance is increased. This migration is independent o